Preliminary Batch Cultures on the Recombinant Strain of Bacillus megaterium for Mosquito Larvicidal Toxin Production - Damrianant, Somchit (Thai Journal of Science and Technology, 2015)
Abstract The spontaneous mutant of Bacillus megaterium pWH1520TK recombinant strain harboring a 93 kDa fusion binary toxin gene of mosquito larvicidal activity, has been preliminarily studied in batch cultures. The fermentation medium was Luria Bertaini medium supplemented with 20 mg/ml of tetracycline and 0.5 % xylose addition to induce expression of the toxin gene. Maximum dry weight and maximum toxin produced have been found at 20 h and 24 h, respectively. The toxin levels stayed high over 60 h, and decreased remarkably at 72 h, perhaps indicating some protease activity. Bioassays were also carried out to confirm mosquito larvicidal activity of the batch fermentation samples. LD50 values were in a range between 2.86-3.11 x 103 cells/ml, indicating a down mutation to low toxicity and instability of toxin production, when compared to the LD50 value of 2.31 x 102 cells/ml for the original mutant. The results show that the recombinant strain of B. megaterium, with further studies on its gene harboring stability and toxin optimization, could be a promising host expressing mosquito larvicidal toxin. Keywords: fusion binary toxin gene; batch fermentation; recombinant strain; Bacillus megaterium; mosquito larvicidal activity